Egyptian public diplomacy: Past performance and future strategies - Abd El-wahed, Manar (AUC Knowledge Fountain, 2016)

(untitled)
This study aims to explore whether the types of Egyptian public diplomacy, if any, follow strategies, content, and priorities of new public diplomacy by analyzing public diplomacy strategies followed by the two of main informational bodies in the Egyptian state: the State Information Service (SIS), and the public diplomacy division in the Ministry of Foreign Affairs (MFA). The study advances a theoretical framework designed to help find a connection between strategies followed by public diplomacy institutions and agenda-building function of those institutions. The analysis reflected the lack of strategic planning in the two institutions to reach and influence foreign publics. Findings proposed that the main communication strategies in the SIS and MFA related to media relations and adopting reactive approaches to counter negative media coverage about the country in foreign media. A set of recommendations were introduced in a search for enhanced public diplomacy structure with more effective strategies to properly communicate with the international community